Nutty carbon: morphology replicating hard carbon from walnut shell for na ion battery anode - Wahid, M.; Gawli, Y.; Puthusseri, D.; Kumar, A.; Shelke, M. V.; Ogale, S. (ACS Omega, 2017)
<div id="absImg" style="position: relative; margin: 0px; padding: 5px; border: 1px solid rgb(204, 204, 204); border-radius: 5px; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; text-align: center; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;"><img alt="Abstract Image" src="http://pubs.acs.org/appl/literatum/publisher/achs/journals/content/acsodf/2017/acsodf.2017.2.issue-7/acsomega.7b00633/20170713/images/medium/ao-2017-00633k_0006.gif" style="border: 0px; max-width: 100%;"> <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Efficient Na ion intercalation/deintercalation in the semigraphitic lattice of a hard carbon derived from the walnut shell is demonstrated. High-temperature (1000 °C) pyrolysis of walnut shells under an inert atmosphere yields a hard carbon with a low surface area (59 m2 g–1) and a large interplanar c axis separation of 0.39–0.36 nm as compared to 0.32 nm for graphite, suitable for Na ion intercalation/deintercalation. A stable reversible capacity of 257 mAh g–1 is observed at a current density of 50 mA g–1 for such nutshell-derived carbon (NDC) with an impressive rate performance. No loss of electrochemical performance is observed for high current cycling (100 mA g–1 → 2 A g–1 → 100 mA g–1). Additionally, the NDC shows remarkably stable electrochemical performance up to 300 charge–discharge cycles at 100 mA g–1 with a minimal drop in capacity.
Keywords: Batteries; Biological and Medicinal chemistry; Biological materials; diffraction; Electric Properties; Electrode-electrolyte interface; spectra; Surface structure; Thermal properties